Peran Pengambilan Keputusan Intuitif pada Pengembangan Strategi Bisnis Wisata Kuliner di Tanjungpinang - Dewi Melinda Hutabarat; Pipit Irawati; Marnia M (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of culinary tourism as one of the fastest-growing tourism segments requires strategic decision-making that is responsive to tourist preferences, market dynamics, and local culture. This article examines the role of intuitive decision-making in formulating and implementing business strategies for culinary tourism, with a case focus on Tanjungpinang. Using a literature review method, the article synthesizes theories and empirical findings on intuition in managerial decision-making as well as practices in culinary tourism development in Indonesia and the Riau Islands region. The results show that intuitive decisions—shaped by experience, tacit knowledge, and rapid information processing—play an important role when information is limited, time is constrained, or market conditions change quickly. However, intuition becomes effective when combined with data-based verification mechanisms and stakeholder collaboration. Practical implications for business actors and local policymakers include: (1) strengthening the experiential capabilities of culinary business managers; (2) integrating intuition with practices of monitoring visitor data and tourist feedback; and (3) developing culinary experience packages that highlight the local uniqueness of Tanjungpinang. Suggestions for future research emphasize empirical field studies on the relationship between intuition, business performance, and tourist satisfaction in Tanjungpinang.